Conceding composition: a crooked history of composition's institutional fortunes - Skinnell, Ryan, author; Utah State University Press, publisher (Colorado State University. Libraries, 2016)
A wide-ranging historical examination of composition's evolving institutional value in American higher education over the course of nearly a century while raising new questions about why composition exists in the university, how it exists, and how teachers and scholars might productively reconceive first-year.
Keywords: Composition (Language arts) -- Study and teaching (Higher) -- History; Rhetoric -- Study and teaching -- History